On (λ,μ,ζ)-Zweier ideal convergence in intuitionistic fuzzy normed spaces - Granados, Carlos; Das, Suman (Yugoslav Journal of Operations Research, 2022)
In this paper, we introduce and study a new type of convergence which is namely (λ,μ,ζ)-Zweier convergence and (λ,μ,ζ)-Zweier ideal convergence of triple sequences x = (xijk) in intuitionistic fuzzy normed spaces (IFNS), where λ= (λn), μ = (μm) and ζ = (ζ p) are three non-decreasing sequences of positive real numbers such that each tend to infinity. Besides, we define and study (λ,μ,ζ)-Zweier Cauchy and (λ,μ,ζ)- Zweier ideal Cauchy sequences on the said space and establish some relations among Them. problem.